NATO enlargement and relations between Serbia and Montenegro and Bulgaria and Romania - Fatić Aleksandar (Međunarodni Problemi, 2003)
The discussion of bilateral relations in modern international relations is usually in the shadow of the new character of global international politics, which is mediated through the large international relations. Bilateral diplomacy is slowly giving way to multilateral diplomacy in the solving of most international issues, including those that have been traditionally perceived as belonging exclusively to the domain of state sovereignty. However, bilateral relations remain crucial in situations where integration processes into large international bodies encounter obstacles and problems. The current development of bilateral diplomacy between Serbia and Montenegro on the one, and Bulgaria and Romania, on the other hand, serves predominantly the purposes of regional harmonisation that will eventually lead to NATO and EU accession, and this process also serves to iron out not so infrequent problems and dissonances in the recent history of bilateral relations, especially between Bulgaria and the former FRY, and particularly during the NATO bombing of FRY in the Spring of 1999. Today, however, all three countries have proclaimed the EU and NATO accession projects as the top priorities of their foreign policies. In the course of pursuit of their accession policies, Bulgaria and Romania have realised that the so-called “beauty contest” approach, namely the countries' insistence on their own qualifications for membership in the EU and NATO, as opposed to the qualifications of the other countries of the region, is largely futile, and they have opted instead for a regional cooperation approach. The latter approach is consistent with the founding principle of regionalism in the internal organisation of the European Union, and this principle includes, among others, the sub-principle of subsidiarity, whereby all decisions are made on the lowest hierarchical level possible, preferably on the level of European regions. This approach implies that countries that are candidates for membership in the EU must first demonstrate the ability to cooperate and integrate regionally, and this is why Romania and Bulgaria, as well as Serbia and Montenegro, have now refocused their efforts on mutual bilateral relations within the context of NATO (and EU) accession.